Advancing Sustainable Livelihoods and Societal Development: An Integrated Approach for Islamic Charity Organizations - LONE, AIJAZ BASHIR (International Journal of Islamic Economics and Governance, 2025)
Islam provides different ways to fulfil the objectives of eradicating poverty and establishing social and economic justice. Some of the best-known tools to raise funds for poverty reduction and social and economic justice in Muslim communities are obligatory or voluntary, such as Zakat, Waqf, Sadaqah, Qard al-Hassan, etc. These funds are mostly collected by Islamic charity organizations (NGOs) to be distributed or spent on various causes. For example, funds are commonly employed through Islamic social finance in Muslim communities for a variety of reasons, including to reduce the vulnerability of the poor, promote sustainable livelihoods, achieve the common good, mitigate humanitarian crises, etc. The paper discusses these tools of Islamic social financing and the employment of funds through Islamic charity organizations for the common good. The paper also discusses the compatibility of the proposed structure and functioning of Islamic charity organizations to utilize the funds in a more efficient way to achieve a suitable livelihood and development in society.